The Effect of Product Quality and Price on Customer Loyalty through Customer Satisfaction as an Intervening Variable at Warung Makan Popina, Southeast Pontianak - Qaisa Amanda Putri; Neni Triana M (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of product quality and price on customer loyalty with customer satisfaction as a mediating variable at Warung Makan Popina. This study uses a quantitative approach with an associative design. The sampling technique applied was purposive sampling, with the research population including all customers who had visited and made purchases at Warung Makan Popina. The number of respondents used in this study was 100 consumers who met the predetermined criteria. Data analysis was carried out using the Structural Equation Modeling (SEM) method with the assistance of SmartPLS 3 software. Model testing included evaluation of the outer model consisting of convergent validity testing, discriminant validity testing, Average Variance Extracted (AVE) values, and reliability testing. Furthermore, the inner model evaluation was conducted through testing the R-Square value, direct effects, and indirect effects. The results showed that product quality and price directly affect customer satisfaction. In addition, customer satisfaction and price were proven to have a direct effect on customer loyalty. However, other direct testing results indicated that product quality does not have a direct effect on customer loyalty. Furthermore, based on the results of indirect testing, product quality and price affect customer loyalty through the mediating role of customer satisfaction.